Halal in food industry around the globe - Mansoor Abdul Hamid; Yeap Chi Hong; Oslida Martony; Mazarina Devi (Journal of Halal Science and Technology, 2022)
The concept of Halal is well understood and practised by Muslims. Muslims are restricted to only consuming foods that are certified as Halal. However, today, the consumption of Halal food is no longer regarded only as a religious obligation for Muslims but is also sought after by non-Muslim society due to the rising health concern as Halal foods are often classified as ones that have high quality from the perspectives of safety and hygiene. The fact that there are already 1.9 billion Muslims in the globe is indisputable proof that the halal food sector is promising for both Muslim and non-Muslim participants in the industry. Many Muslim-minority countries, such as New Zealand, Canada, the United Kingdom (UK), Australia, the United States of America (USA), India, and Argentina are also exporting Halal foods to foreign countries as they believe that this can generate substantial revenue for them. Nevertheless, low awareness of the concept of halal, uncertainties regarding the ingredients used in the products, and misleading information on a product’s packaging are a few of the challenges in the Halal food industry. In order to popularize the concept of Halal to more non-Muslims, the authority, plays a significant role in this scenario by providing public information related to the concept of Halal as well as taking more stern actions in combating the occurrence of Halal food frauds.